CORDYCEPIN AS A LEAD BIOACTIVE MOLECULE FROM CORDYCEPS: MOLECULAR MECHANISMS AND CLINICAL PROSPECTS - A, Rakesh S; N, Anusha B; C, Prathiksha C; Md, Mohd. Yosuf; H, Bhagya V; C, Bhumika B; S, Gagan H (International Journal of Pharma and Bio Sciences, 2026)
Cordycepin (3′-deoxyadenosine), a naturally occurring nucleoside analog predominantly isolated from Cordyceps species, has attracted significant scientific interest as a lead bioactive molecule with broad pharmacological potential. Structurally analogous to adenosine but lacking a 3′-hydroxyl group, cordycepin interferes with nucleic acid synthesis, RNA polyadenylation, and multiple intracellular signaling pathways. Extensive preclinical evidence demonstrates that cordycepin exerts diverse biological activities, including anticancer, anti-inflammatory, immunomodulatory, metabolic, cardioprotective, and neuroprotective effects. These actions are mediated through modulation of key molecular pathways such as AMP-activated protein kinase (AMPK), NF-κB, MAPKs, PI3K/Akt, mTOR, and mitochondrial signaling networks. Despite robust mechanistic and experimental support, clinical translation of cordycepin remains limited due to challenges including poor oral bioavailability, rapid degradation by adenosine deaminase, lack of standardized formulations, and scarcity of well-controlled human clinical trials using purified compound. Recent advances in biosynthesis, formulation strategies, and delivery systems offer promising avenues to overcome these limitations. This review critically summarizes the chemical characteristics, biosynthesis, molecular mechanisms, pharmacological activities, clinical prospects, and translational challenges of cordycepin, highlighting future research directions required to advance it from a promising natural product to a clinically viable therapeutic agent for complex chronic diseases.